Program Edukasi Lingkungan Melalui Pemanfaatan Limbah Air Untuk Budidaya Ikan di SMP 2 Cangkringan - Prasetya Adi; Arusmalem Ginting (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2026)
Abstract: This community service program aims to raise environmental awareness and food security by utilizing ablution wastewater as a medium for catfish cultivation at Cangkringan 2 State Junior High School. This activity was motivated by the volume of ablution water wasted daily in the school environment, which is actually still suitable for non-consumption purposes. Through an educational and practical approach, this program teaches students the concept of water recycling, simple technology, and basic catfish cultivation skills. Implementation methods include counseling, training, technical assistance, and evaluation of cultivation results. In addition to providing new knowledge, this activity also fosters environmental awareness and food independ-ence among students. Initial results show an increase in students' understanding of water conservation and their ability to manage a sustainable fish cultivation system. This program is expected to become a model for environmentally-based contextual learning while contributing to the development of sustainable education and strengthening food security at the school level. Keywords: catfish; education; environment Abstrak: Program pengabdian masyarakat ini bertujuan untuk meningkatkan kesadaran lingkungan dan ketahanan pangan melalui pemanfaatan limbah air wudu sebagai me-dia budidaya ikan lele di SMP Negeri 2 Cangkringan. Kegiatan ini dilatarbelakangi oleh volume air wudu yang terbuang setiap hari di lingkungan sekolah, yang sebenarnya masih layak digunakan untuk kebutuhan nonkonsumsi. Melalui pendekatan edukatif dan praktis, program ini mengajarkan siswa konsep daur ulang air, teknologi sederhana, serta keterampilan dasar budidaya ikan lele. Metode pelaksanaan meliputi penyuluhan, pelatihan, pendampingan teknis, dan evaluasi hasil budidaya. Selain memberikan pengetahuan baru, kegiatan ini juga menumbuhkan karakter peduli lingkungan dan kemandirian pangan di kalangan siswa. Hasil awal menunjukkan peningkatan pemahaman siswa terhadap konservasi air dan kemampuan mereka dalam mengelola sistem budidaya ikan secara berkelanjutan. Program ini diharapkan menjadi model pembelajaran kontekstual berbasis lingkungan sekaligus berkontribusi terhadap pembangunan pendidikan berkelanjutan dan penguatan ketahanan pangan di tingkat sekolah. Kata kunci: edukasi;ikan lele;lingkungan